Evaluación y Clasificación de la Calidad de Varios Cuerpos de Agua en la Península de Osa - Calvo-Brenes, Guillermo; Mora-Molina, Jesús (Instituto Tecnológico de Costa Rica, 2010)
Water is not only essential for the preservation of live, but also for the conservation of flora and fauna of the region. Its quality and conservation is closely related to economical and social activities in an inevitable way, as well as health issues. Península de Osa is acknowledged as the richest biological zone of Mesoamerica. The diversity of its habitat and the biological richness is rarely found in such small areas. This exotic territory, named Península de Osa, is not inmune to enviromental attacks due to fragmentation and destruction of the habitat, deforestation and misused of land, illegal extraction of resources, like gold; and the population increase around the Peninsula. The actual diagnostic is focused on knowing the actual situation and possible risks of contamination of several rivers in Osa. Several rivers were sampled in PiedrasBlancas, a town close to Chacarita, as well as Rincón, Puerto Jiménez and Drake Bay, the last three of them belonging to Península de Osa. The waters quality was analyzed based on theClassification Holland Index. Even though the area characteristics, there is already light contamination present, according to density population; but the effect will also depend on soil type, urban development and vegetation coverage. Typical examples of these variability are the towns of Puerto Jiménez, PiedrasBlancas and Drake Bay.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Química, 2010
Keywords: Precipitación; Análisis; Contaminación; Densidad; Biodiversidad